Investigation of the optical coatings on the dkdp single ctystals by x-ray photoelectron spectroscopy - Loya, V.Yu.; Lada, A.V.; Puga, P.P.; Gritsyna, V.T. (Физическая инженерия поверхности, 2004)
Magnesium fluoride and tellurium oxide were used for fabrication of the protective and antireflective coatings on the DKDP crystals. The variation of the technology of coating deposition leads to changes of surface composition of coatings which was studied by using the X-ray photoelectron spectroscopy (XPS). The XPS data allow us to conclude that carbon and its compounds, as well as oxygen resulting in the oxide formation, are the main impurities introduced at the different stages of coating deposition. The results of paper testify the fact that the ion beam processing of the DKDP single crystals with film coatings deposited onto their working surfaces facilitates the recovery of the initial composition of the film under deposition, the removal of impurities from the film surfaces that, in turn, contributes to the improvement of mechanical properties of the coating and its consolidation. Для одержання захисних і просвітляючих покриттів кристалів ДКДР використовувалися фторид магнію та оксид телуру. Модифікація технології нанесення покриттів призвела до зміни складу поверхні покрить, що досліджувалися методом рентгенівської фотоелектронної спектроскопії (РФС). Дані РФС дозволяють зробити висновок, що вуглець та його сполуки, а такожкисень, що призводить до утворення оксидів, є основними домішками, які вводяться на різних етапах нанесення покриттів. Результати роботи свідчать на користь того, що обробка монокристалів ДКДР з плівками, осадженими на їх робочі поверхні, за допомогою іонного пучка сприяє відновленню вихідного складу осаджуваної плівки, вилученню домішок з її поверхні, що, в свою чергу, покращує механічні властивості покриття і його експлуатаційні характеристики. Для получения защитных и просветляющих покрытий кристаллов ДКДР использовались фторид магния и оксид теллура. Модификация технологии нанесения покрытий привела к изменению состава поверхности покрытий, исследуемых методом рентгеновской фотоэлектронной спектроскопии (РФС). Данные РФС позволяют заключить, что углерод и его соединения, а также кислород, приводящий к образованию оксидов, являются основными примесями, вводимыми на различных этапах нанесения покрытий. Результаты работы свидетельствуют в пользу того, что обработка монокристаллов ДКДР с пленками, осажденными на их рабочие поверхности, с помощью ионного пучка способствует восстановлению исходного состава осаждаемой пленки, удалению примесей с ее поверхности, что, в свою очередь, улучшает механические свойства покрытия и его эксплуатационные характеристики.